2010
DOI: 10.2967/jnumed.110.076695
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Bicyclic Somatostatin-Based Analogs: A Novel Class of Potential Radiotracers for SPECT/PET of Neuroendocrine Tumors

Abstract: A variety of radiolabeled somatostatin analogs have been developed for targeting of somatostatin receptor (sst)-positive tumors. Bicyclic somatostatin-based radiopeptides have not been studied yet. Hypothesizing that the introduction of conformational constraints may lead to receptor subtype selectivity or may help to delineate structural features determining pansomatostatin potency, we developed and evaluated first examples of this new class of potential radiotracers for imaging or therapy of neuroendocrine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The final products, CB-TE2A-LM3, NODAGA-LM3, and DOTA-LM3, were purified by semipreparative HPLC and characterized by electrospray ionization mass spectrometry and RP-HPLC. 68 Ga-NODAGA-LM3 and 68 Ga-DOTA-LM3 were prepared in sodium acetate buffer (0.2 mol/L, pH 4.0), at RT for 10 min (NODAGA-LM3) or at 95°C for 8 min (DOTA-LM3), as described elsewhere (20). 64 Cu and 68 Ga radiopeptides were prepared without any postlabeling purification step.…”
Section: Synthesis Of Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…The final products, CB-TE2A-LM3, NODAGA-LM3, and DOTA-LM3, were purified by semipreparative HPLC and characterized by electrospray ionization mass spectrometry and RP-HPLC. 68 Ga-NODAGA-LM3 and 68 Ga-DOTA-LM3 were prepared in sodium acetate buffer (0.2 mol/L, pH 4.0), at RT for 10 min (NODAGA-LM3) or at 95°C for 8 min (DOTA-LM3), as described elsewhere (20). 64 Cu and 68 Ga radiopeptides were prepared without any postlabeling purification step.…”
Section: Synthesis Of Conjugatesmentioning
confidence: 99%
“…The internalization and dissociation rates of 64 Cu-CB-TE2A-LM3 and 64 Cu-NODAGA-LM3 were studied in HEK-sst2 cells seeded in 6-well plates, as described previously (18,20). Briefly, the radiopeptide was added to the medium (0.25 pmol/mL), and the cells were incubated at 37°C.…”
Section: Receptor-binding Internalization and Dissociation Studiesmentioning
confidence: 99%
“…A recent example is the development of bicyclic somatostatin-based radiopeptides, a neglected family of radiopeptides, developed by Fani et al (24). These molecules have fast background clearance and therefore high tumor-to-normal organ ratios.…”
Section: Future Developments New Strategiesmentioning
confidence: 99%
“…One of the first reports describing 68 Ga-and 64 Cu-labeled sst2 antagonists indicated the high potential of these radiopeptides in PET/CT [75]. Translational aspects related to peptide receptor radionuclide therapy (PRRT) and imaging with antagonist were also addressed.…”
Section: Antagonists Vs Agonistsmentioning
confidence: 99%
“…However, the application of similarly developed 111 In-DOTANOC-ATE (1-NaI [63]. Fani et al (2010) reported the development of bicyclic somatostatin analogs with affinity to sst2, sst3 and sst5, such as AM3 (DOTA-)Tyr-cyclo(DAB-Arg-cyclo(Cys-Phe--D-Trp-Lys-Thr-Cys)) which showed fast background clearance and high tumor to non-tumor ratios which might be ideal for imaging with short lived radionuclides such as 68 Ga [64]. Pan-somatostatin radiopeptides with high affinity binding for all five receptor subtypes have also been developed.…”
mentioning
confidence: 99%